Managing the trade-off between autonomy and task interdependence in creative teams: The role of organizational-level cultural control - Grabner, Isabella; Klein, Aleksandra; Speckbacher, Gerhard (Accounting, Organizations and Society, 2022)
In the creative industries, creative output is often produced in temporary project teams, staffed with employees from within the organization. In this study we make two main contributions regarding the management of creative performance in such teams. First, we provide evidence for a fundamental trade-off inherent in creative teamwork. Team creativity benefits both from high team member autonomy and high task interdependence, but when team leaders give higher autonomy to team members then this undermines the positive effect of a more interdependent design of teamwork on team creativity, and vice versa. Second, we argue that cultural control at the organizational level is an effective means to resolve this team-level trade-off and to enable teams to leverage both high autonomy and high task interdependence for higher team creativity. We test our hypotheses using survey data collected at three different organizational levels (team members, team leaders, and agency heads) from 372 individuals of 101 temporary project teams within 53 advertising agencies, and find evidence consistent with our predictions.